Effects of NOL8 on cell proliferation, migration and invasion of oral squamous cell carcinoma - WANG Xiaoxiao, CHEN Xi, LI Minmin, SONG Ning, SUN Dongyuan, JIANG Yingying (Zhongguo aizheng zazhi, 2023)
Background and purpose: Oral squamous cell carcinoma (OSCC) is the most common subtype of head and neck squamous cell carcinoma (HNSCC), and its pathogenesis is unclear. Nucleolar protein 8 (NOL8), as one of the RNA-binding protein (RBP), plays a key role in the occurrence and development of many kinds of tumors, however its role in OSCC is not clear. This study aimed to investigate the expression level of NOL8 in OSCC and its effects on the proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) of OSCC. Methods: The expression of NOL8 in HNSCC was analyzed online by gene expression profiling interactive analysis 2 (GEPIA2), tumor immune estimation resource (TIMER), the University of Alabama at Birmingham cancer data analysis portal (UALCAN) and the encyclopedia of RNA interactomes (ENCORI). The mRNA expression level of NOL8 in OSCC cells was detected by real-time fluorescence quantitative polymerase chain reaction (RTFQ-PCR). siRNA interference technique was used to knock down the expression of NOL8 in CAL-27 cells to form NOL8 knockdown group (si-NOL8-1, si-NOL8-2) and negative control group. CAL-27 and HN6 cells were overexpressed with NOL8 by lentivirus transfection technique to form NOL8 overexpression group and negative control group. Cell counting kit-8 (CCK-8) assay, scratch healing assay and transwell assay were used to detect the effect of NOL8 expression on the proliferation, migration and invasion of OSCC cells. Western blot assay was used to detect the effect of NOL8 on the expression of EMT-related genes including E-cadherin, vimentin and N-cadherin. The effect of NOL8 on the proliferation of OSCC cells in vivo was examed by xenograft formation assays. Results: The online analysis of GEPIA2, TIMER, UALCAN and ENCORI showed that the expression of NOL8 was higher in HNSCC than in normal tissues, and the expression of NOL8 in OSCC was significantly higher than in normal control cells. The relative expression of NOL8 in CAL-27 cells transfected with si-NOL8-1 and si-NOL8-2 was significantly lower compared with the negative control group. The results of CCK-8 assay, scratch healing assay and transwell assay showed that the proliferative ability, cell migration rate and invasion number of CAL-27 cells were significantly decreased after knockdown of NOL8 expression. The relative expression of NOL8 in CAL-27 and HN6 cells transfected with NOL8 was significantly higher compared with the control group. The proliferative ability, cell migration rate and invasion number of CAL-27 and HN6 cells in the overexpression NOL8 group were significantly higher compared with the negative control group. The results of Western blot showed that in CAL-27 cells, the expression of E-cadherin increased and the expressions of N-cadherin and vimentin decreased after NOL8 knockdown, while in CAL-27 and HN6 cells, the expression of E-cadherin decreased and the expressions of N-cadherin and vimentin increased after NOL8 overexpression. The xenograft formation assays showed that the weight of tumor was significantly higher in NOL8 overexpression group than in NOL8 control group. Conclusion: NOL8 is highly expressed in OSCC and can promote the proliferation, migration and invasion of OSCC, which may be related to the process of EMT.